Expression in Escherichia coli of a cloned DNA sequence encoding the pre-S2 region of hepatitis B virus. - Offensperger, W (1985)
A DNA sequence encoding the entire pre-S2 region (amino acids 120-174; serotype ayw) of human hepatitis B virus envelope protein has been inserted into the lacZ gene of the plasmid pSKS105 yielding a recombinant, pWS3. Lac+ colonies of the Escherichia coli M182 delta (lacIOPZYA), isolated after transformation with pWS3, produced a pre-S2 peptide-beta-galactosidase fusion protein. This fusion protein, which comprised as much as 3% of the total bacterial protein, was purified to greater than 90% homogeneity by affinity chromatography on p-aminophenyl-beta-D-thiogalactoside-Sepharose. It is immunoprecipitable with rabbit antibodies to a synthetic peptide corresponding to amino acids 120-145 of the pre-S2 region of serotype adw [pre-S(120-145)] or with antibodies to hepatitis B virus. pre-S(120-145) completely blocked the binding of either antibody to the pre-S2 peptide-beta-galactosidase fusion protein. These results indicate that there are antigenic determinants on the fusion protein that are closely related to, if not identical to, determinants on synthetic pre-S(120-145) and on pre-S2 sequences of native hepatitis B virus particles. Thus, bacteria transformed with pWS3 can provide an abundant source of pre-S2-beta-galactosidase fusion protein, which may prove useful either as a diagnostic reagent possessing marker enzyme activity suitable for ELISA tests or as an immunogen with potential to contribute to active prophylaxis of hepatitis B.